Pelteobagrus fulvidraco culturing method - ZHAO AI; XIN GUANGQUAN; WANG HONGYING; GAO JIANZHONG; HE BINBIN (2016)
The invention provide a pelteobagrus fulvidraco culturing method. The pelteobagrus fulvidraco culturing method comprises the following steps of 1, pond cleaning and sterilization: remaining a little of water in a pond, dissolving quicklime into water, sterilizing the pond, waiting for 1 to 2 days, then turning pond silt by using an iron harrow, and making lime slurry be sufficiently mixed with sludge; 2, water injection and fertilization: after the pond is sterilized, starting injecting water into the pond, subsequently fertilizing for the pond, and cultivating pelagic organisms; 3, in-pond net cage arranging: arranging net cages side by side in the pond; 4, pelteobagrus fulvidraco breeding: certainly paying attention to the regulation of a temperature difference when fries are bred, wherein a breeding specification per square meter is 100 to 200 pelteobagrus fulvidraco fries each of which is approximately 20 grams in weight; 5, pelteobagrus fulvidraco feeding: generally feeding twice a day, adopting a spaced